A Lower-Energy Pathway for the Creation of Multifunctional Silicon Suboxide Films - Rangel, Rita de Cássia [UNESP]; Ribeiro, Rafael Parra [UNESP]; de Souza, Maria Eliziane Pires; Spigarollo, Danielle Cristina Fernandes da Silva [UNESP]; de Souza, Gelson Biscaia; Rangel, Elidiane Cipriano [UNESP] (MDPI, 2025)
The possibility of inducing structural crosslinking and densification of plasma-deposited SiOx networks by controlling low-energy reaction mechanisms was investigated. For this, films were deposited for 300 s from HMDSO (2%), O2 (86%) and Ar (12%) mixtures at a working pressure of 15.7 Pa. A radiofrequency signal was used to excite the plasma in a configuration so as to not deliberately induce ion bombardment of the growing layers. The plasma excitation power was varied (100 to 300 W) to promote changes in the deposition mechanisms, which were investigated from deposition rate and layer thickness, chemical structure, elemental composition, topography, roughness, hardness, elastic modulus, corrosion potential, corrosion current density and porosity of the films. Under the experimental conditions studied, inorganic SiOx thin films (x = 1.8–1.9) with a low carbon content were deposited. The increase in the applied power during the deposition process reduced the number of silanol groups in the coatings, due to dangling bonds recombination by structural crosslinks, which avoided hydroxyl incorporation and silanol formation. As a consequence, the structure became harder, more compact and corrosion resistant.
Keywords: corrosion resistance; crosslinking; HMDSO; mechanical properties; plasma deposition; SiOx